Maternal participation patterns in a community-based growth monitoring programme in North-East Brazil - Correia, Luciano Lima (1988)
Maternal participation patterns in a community-based growth monitoring programme in North~East Brazil were analyzed. The cultural, socio- economic and health-related characteristics of participant and non- participant mothers and children were identified and compared. I.t was found that 30% of mothers and their respectivo children living within the programme's catchment area did not participate in the growth- monitoring programme. Participation was higher in urban than rural areas. Mothers were asked their reasons for non-participation in the programme and in 30% of cases claimed that they had never been invited to participate. Non-participant mothers showed higher rates of illiteracy, non-use of available health resources, child deaths and hospitalizatlon that participant mothers. No significant difference in relation to age, family income or the nutritional status of their children was observed between the two groups of mothers. It was concluded that a large number of children of mothers from the non- participant group were highly at risk and that steps to reach them with the growth-monitoring programme should be taken. Suggestions for achieving this objective were formulated.